1987
DOI: 10.1002/pssb.2221390111
|View full text |Cite
|
Sign up to set email alerts
|

IR Spectroscopy and Structure of RF Magnetron Sputtered a‐SiC:H Films

Abstract: Amorphous hydrogenated silicon carbide (a-Sic : H) films are prepared by magnetron sputtering of crystalline silicon in an argon-hydrogen-methane atmosphere. The specific absorption modes (wagging, rocking, deformation, stretching) of the Sic-, (CH,),C/Si-(n = 1, 2, 3; m = 2, 3), and SiH,-(m = 1,2) groups are assigned and analyzed. The composition of the films is determined by nuclear reaction techniques. Structural, electrical, and optical properties of the films show characteristic changes near an alloy comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 39 publications
(5 reference statements)
3
21
0
Order By: Relevance
“…The signals around 825 cm -1 and 856 cm -1 can be due to both GeH 2 and to GeH 3 bending modes and to GeCH n (n=1,2) wagging modes. [1,[40][41][42] It is noteworthy that, in agreement with the above attributions of stretching signals between 2800 cm -1 and 3000 cm -1 , no band is observed in the range 770-780 cm -1 which is generally attributed to wagging vibration of the CH 3 group bound to germanium. This confirms that our solids contain only mono and dihydrocarbon groups.…”
Section: Morphology Bonding and Structuresupporting
confidence: 81%
See 2 more Smart Citations
“…The signals around 825 cm -1 and 856 cm -1 can be due to both GeH 2 and to GeH 3 bending modes and to GeCH n (n=1,2) wagging modes. [1,[40][41][42] It is noteworthy that, in agreement with the above attributions of stretching signals between 2800 cm -1 and 3000 cm -1 , no band is observed in the range 770-780 cm -1 which is generally attributed to wagging vibration of the CH 3 group bound to germanium. This confirms that our solids contain only mono and dihydrocarbon groups.…”
Section: Morphology Bonding and Structuresupporting
confidence: 81%
“…[37,39] In the range 1200-1350 cm -1 three weak bands are found, and on the basis of observations by Brown et al [48] and Tschamler [49] on n-paraffins, we attribute these signals to the CH 2 wagging mode. The band observed in the region between 950 cm -1 and 1200 cm -1 was attributed to the rocking or wagging modes of (CH m ) n -C/Ge (m=1,2; n=1-3) groups, [1,32,41,43] and to the C-C skeletal stretching vibrations. [21,37] In the wavenumber region between 500 cm -1 and 900 cm -1 , the interpretation of the spectra is complicated by the presence of several signals leading to broad overlapped bands due to the GeCH n (n=1,2) and GeH 2 bending modes, the Ge-C stretching, the CH 2 rocking, and Ge-H wagging modes.…”
Section: Morphology Bonding and Structurementioning
confidence: 93%
See 1 more Smart Citation
“…It is known from literature, that the peak at 2265 cm À 1 is clearly attributed to Si-H x vibration mode with the presence of oxygen around the Si atom (Holm & Roberts, 2007a). Surface oxidation due to the exposure to ambient air can clearly be observed by the broad peak at 1170 cm À 1 (Rübel et al, 1987). Finally, the band at 1640 cm À 1 can be associated with hydroxyl groups, which are bound to the silicon surface (Si-OH vibrational mode, Li, Swihart, & Ruckenstein, 2004b).…”
Section: Characterization Of Sinp Powder Propertiesmentioning
confidence: 91%
“…[32] Theoretical Study of the GeC 2 H n (n ‫؍‬ 4؊7) Species so the reaction forming GeH 2 radicals should be energetiIn order to determine the most probable reaction pathcally favoured. Moreover, it has been observed that GeH 2 ways leading to the formation of the condensed-phase prodfurther decomposes according to Equations 6 and 7, which ucts, ab initio theoretical calculations on the products obcompete with each other in the ratio 9:1 [32] and suggest that tained from the previous reactions have been performed. the Ge and GeH species must also be considered in the Since in the radiolysis of ethylene the products maintaining products formation.…”
Section: Radiolysis Of Geh 4 /C 2 H 4 Mixturesmentioning
confidence: 99%